Chemo-Immunotherapy Regimes for Recurrent or Metastatic Nasopharyngeal Carcinoma: A Network Meta-Analysis and Cost-Effectiveness Analysis - Zhu, Youwen; Liu, Kun; Ding, Dong; Wang, Kailing; Liu, Xiaoting; Tan, Xiao (Frontiers in Pharmacology, 2022)
Introduction: In 2021, two phase III clinical trials confirmed that toripalimab or camrelizumab combined with gemcitabine and cisplatin (TGP or CGP) provide more benefits in the first-line treatment of R/M NPC than GP. Fortunately, TGP and CGP were recently approved as first-line treatments for cases experiencing R/M NPC by the China National Medical Products Administration in 2021. However, due to the high cost and variety of treatment options, the promotion of chemo-immunotherapeutics in the treatment of R/M NPC remains controversial. Therefore, we performed a cost-effectiveness assessment of the two newly approved treatment strategies to assess which treatments provide the greatest clinical benefits at a reasonable cost. Methods: A cost-effectiveness analysis and network meta-analysis network meta-analysis was conducted based on the JUPITER-02 and CAPTAIN-first Phase 3 randomized clinical trials. A Markov model was expanded for the evaluation of the effectiveness and cost of TGP, CGP, and GP chemotherapy with a 10-years horizon and measured the health achievements in quality-adjusted life-years (QALYs), incremental cost-effectiveness ratios (ICERs), and life-years (LYs). We constructed a treatment strategy and other parameters based on two clinical trials and performed one-way and probabilistic sensitivity experiments for the evaluation of the uncertainty in the model. Results: For the model of patients with treatment-R/M NPC, TGP was associated with a total cost of 48,525 and 2.778 QALYs (4.991 LYs), leading to an ICER of 15,103 per QALY (10,321 per LY) compared to CGP. On comparing the GP chemotherapy, we found TGP and CGP incurred substantial health costs, resulting in ICERs of 19,726 per QALY and 20,438 per QALY, respectively. The risk of adverse events (AEs) and the price of the drugs had significant impacts on the ICER. At the assumed willingness-to-pay (WTP) threshold of 35,673 per QALY, there were approximately 75.8 and 68.5% simulations in which cost-effectiveness was achieved for TGP and CGP, respectively. Conclusion: From the Chinese payer’s perspective, TGP is more possible to be a cost-effective regimen compared with CGP and GP for first-line treatment of patients with R/M NPC at a WTP threshold of 35,673 per QALY.